A Self‐Healing Chemistry‐Enabled Organic Cathode for Sustainable and Stable Sodium‐Ion Batteries - Jinghao Huang; Shi Li; Eric Youngsam Kim; Lei Cheng; Gui-Liang Xu; Khalil Amine; Chunsheng Wang; Chao Luo (Small Structures, 2023)
Sodium‐on batteries (SIBs) are promising alternatives to lithium‐ion batteries (LIBs) because of the low cost, abundance, and high sustainability of sodium resources. Analogous to LIBs, the high‐capacity electrodes in SIBs always suffer from rapid capacity decay upon long‐term cycling due to the particle pulverization induced by a large volume change. Circumventing particle pulverization plays a critical role in developing high‐energy and long‐life SIBs. Herein, tetrahydroxy‐1,4‐benzoquinone disodium salt (TBDS) that can self‐heal the cracks by hydrogen bonding between hydroxyl group and carbonyl group is employed as a cathode for sustainable and stable SIBs. The self‐healing TBDS exhibits long cycle life of 1000 cycles with a high rate capability up to 2 A g−1 due to the fast Na‐ion diffusion reaction in the TBDS cathode. The intermolecular hydrogen bonding has been comprehensively characterized to understand the self‐healing mechanism. The hydrogen bonding‐enabled self‐healing organic materials are promising for developing high‐energy and long‐cycle‐life SIBs.